A Showcase of Green Chemistry: Sustainable Synthetic Approach of Zirconium‐Based MOF Materials - Fu, Jiarui; Wu, Yi‐nan (Chemistry : a European journal, 2021)
Zirconium‐based metal‐organic framework materials (Zr−MOFs) have more practical usage over most conventional benchmark porous materials and even many other MOFs due to the excellent structural stability, rich coordination forms, and various active sites. However, their mass‐production and application are restricted by the high‐cost raw materials, complex synthesis procedures, harsh reaction conditions, and unexpected environmental impact. Based on the principles of “Green Chemistry”, considerable efforts have been done for breaking through the limitations, and significant progress has been made in the sustainable synthesis of Zr−MOFs over the past decade. In this review, the advancements of green raw materials and green synthesis methods in the synthesis of Zr−MOFs are reviewed, along with the corresponding drawbacks. The challenges and prospects are discussed and outlooked, expecting to provide guidance for the acceleration of the industrialization and commercialization of Zr−MOFs. The production and application of Zirconium‐based metal‐organic framework materials are restricted by numerous factors. By embracing green chemistry, green raw materials and green synthesis methods are the keys in sustainable synthesis of Zr−MOFs over last decade. This review summarizes the achievements and looks forward to the future industrialization and commercialization of Zr−MOFs.